(untitled) (Altre Modernità, 2019)
Quantum physics, risen from experimental evidences, shows us a new conception of Nature. Nature seems in some way weird. However, experiments point out singularities, irreducible contradictions, unpredictable events, which cannot be explained by means of universal, causal, deterministic laws for microscopic phenomena. Niels Bohr had deep knowledge of Kierkegaard’s existentialism and he considered it as the key to understand Nature.